Topology and control strategy optimization of an auxiliary resonant commutated pole-based, soft-switching grid-connected inverter - Liu, Chuang; Wang, Yanping (Frontiers in Energy Research, 2023)
With the development of new energy industries such as photovoltaics, microgrids, or distributed energy sources require many DC-AC grid-connected interfaces. Reducing the switching loss of the inverter is important to improve the transmission efficiency of the inverter, reduce the heat generation of the inverter, promote the high frequency and miniaturization of the inverter, and efficiently use the distributed energy. Therefore, considering the wide application of DC-AC power electronic interfaces in microgrid and distributed energy, and to make up for existing deficiencies in traditional hard-switching inverters, an optimal control strategy and topology for an optimal-auxiliary resonant commutated pole (O-ARCP) inverter is proposed in this article. Firstly, this paper introduces the proposed inverter topology and analyzes the operation mode of the circuit with the control strategy. Then simulation experiments in islanding mode are carried out to verify the rationality of the content, and finally simplified experimental verification is carried out based on the simulation results. Simulation and experimental testing reveal that all switches of the proposed topology are in soft-switching mode, which proves the effectiveness of the proposed control strategy and analysis. The analysis and validation of this paper provide assistance in the development of control strategies and structures for soft-switching inverters.